Influence of Phlogopite on the Physico-Mechanical Properties of a Porcelain - Kutty, N. A. A.; Noh, M. Z. (Journal of Science and Technology, 2016)
This research was conducted in order to obtain the optimum composition of phlogopite and sintering temperature of phlogopite in order to get the robust structure of porcelain. Clay, feldspar, quartz, and phlogopite were first sieved, mixed and compacted. Then, the samples were sintered at 1000°C to 1300°C. It is observed that the properties of the porcelain are highly depend on the composition of phlogopite and the sintering temperature of porcelain. Results showed that 10 wt% of phlogopite was the optimum composition and 1200°C was the optimum sintering temperature. The microstructure of the samples were analyzed by using two microscopes and it was evidenced that the pore in the samples were smaller and the structure are denser thus lead to a dense porcelain structure and improves the physical and mechanical properties of the porcelain.